Adventitious rooting in response to long-term cold: a possible mechanism of clonal growth in alpine perennials - Mishra, Priyanka; Roggen, Adrian; Ljung, Karin; Albani, Maria C.; Vayssières, Alice (Frontiers in Plant Science, 2024)
Arctic alpine species experience extended periods of cold and unpredictable conditions during flowering. Thus, often, alpine plants use both sexual and asexual means of reproduction to maximize fitness and ensure reproductive success. We used the arctic alpine perennial Arabis alpina to explore the role of prolonged cold exposure on adventitious rooting. We exposed plants to 4°C for different durations and scored the presence of adventitious roots on the main stem and axillary branches. Our physiological studies demonstrated the presence of adventitious roots after 21 weeks at 4°C saturating the effect of cold on this process. Notably, adventitious roots on the main stem developing in specific internodes allowed us to identify the gene regulatory network involved in the formation of adventitious roots in cold using transcriptomics. These data and histological studies indicated that adventitious roots in A. alpina stems initiate during cold exposure and emerge after plants experience growth promoting conditions. While the initiation of adventitious root was not associated with changes of DR5 auxin response and free endogenous auxin level in the stems, the emergence of the adventitious root primordia was. Using the transcriptomic data, we discerned the sequential hormone responses occurring in various stages of adventitious root formation and identified supplementary pathways putatively involved in adventitious root emergence, such as glucosinolate metabolism. Together, our results highlight the role of low temperature during clonal growth in alpine plants and provide insights on the molecular mechanisms involved at distinct stages of adventitious rooting.